THE RELATIONSHIP BETWEEN HUMAN RESOURCE MANAGEMENT PRACTICES AND EMPLOYEE COMMITMENTS IN SELECTED PRIVATE UNIVERSITIES IN SOUTH-EAST NIGERIA - Enyioko, Chilaka Onyekachi; Adedoyin, Isaac Salami; Egunjobi, Samuel Adesegun; Matthew, Damilola (International Journal of Management and Allied Research (IJMAR), 2025)
The effectiveness of Human Resource Management (HRM) practices is crucial in fostering employee commitment and enhancing job performance in private universities. This study examines the influence of HRM practices on employee commitment in private universities in Southeast Nigeria. The research adopts a descriptive survey design that utilizes both quantitative and qualitative methods to collect and analyze data. A structured questionnaire was administered to academic and administrative staff at selected private universities. The findings reveal that HRM practices, including recruitment and selection, performance management, compensation strategies, employee training, and workplace relations, significantly influence employee commitment. The descriptive analysis indicates a strong emotional connection between employees and their institutions, with a mean score of 4.02 (SD = 0.97). Similarly, 69.6% of respondents expressed no intention to leave their institutions, reflecting a commitment to long-term service. The study also employs ANOVA to assess variations in HRM practices across different universities, yielding a statistically significant F-value of 4.62 (p = 0.002), confirming differences in HRM perceptions among employees. The research highlights the need for private universities to implement standardized HR policies that align employee expectations with institutional goals. Recommendations include enhancing career growth opportunities, improving compensation structures, and fostering a supportive work environment to enhance employee retention and institutional sustainability. These insights contribute to the body of knowledge on HRM practices and their role in shaping workforce stability in private educational institutions